Service Innovations: What the Managers Believe and What the Customers Say - Randhawa, Praneet; Kim, MiRan; Cichy, Ronald F (Routledge, 2016)
Service innovation has become a critical organizational capability. It is crucial to understand not only what service innovations service managers introduce, but also what service innovations help improve customers’ experiences. This study examines the initiatives managers undertake to introduce new services and whether service innovations improve service experiences for the members. In this study, 300 critical incidents were reported by private club general managers/chief operating officers, and 956 were reported by their members in private clubs across the United States. The findings have both theoretical and practical implications.